Spatial dimensions of Soviet repressions in the 1930s : the House of Writers (Kharkiv, Ukraine) - Bertelsen, Olga (2013)
This study examines spatial dimensions of state violence against the Ukrainian intelligentsia in the 1930s, and the creation of a place of surveillance, the famous House of Writers (Budynok Slovo), an apartment building that was conceived by an association of writers “Slovo” in Kharkiv. This building fashioned an important identity for Ukrainian intellectuals, which was altered under state pressure and the fear of being exterminated. Their creative art was gradually transformed into the art of living and surviving under the terror, a feature of a regimented society. The study explores the writers’ behavior during arrests and interrogation, and examines the Soviet secret police’s tactics employed in interrogation rooms.